2020
DOI: 10.1093/biolinnean/blaa091
|View full text |Cite
|
Sign up to set email alerts
|

Proximate and ultimate drivers of variation in bite force in the insular lizardsPodarcis melisellensisandPodarcis sicula

Abstract: Bite force is a key performance trait in lizards because biting is involved in many ecologically relevant tasks, including foraging, fighting and mating. Several factors have been suggested to impact bite force in lizards, such as head morphology (proximate factors), or diet, intraspecific competition and habitat characteristics (ultimate factors). However, these have been generally investigated separately and mostly at the interspecific level. Here we tested which factors drive variation in bite force at the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(32 citation statements)
references
References 107 publications
0
32
0
Order By: Relevance
“…To do so, we measured head dimensions of every specimen, log 10 -transformed them, and calculated the mean distance between males and females along the first axes of a PCA. This measure of sexual dimorphism in head dimensions was previously demonstrated to be a good indicator for the level of sexual competition in these populations (Taverne et al 2020). In vivo bite force was measured for all individuals as described in Taverne et al (2020).…”
Section: Specimens Ecological and Bite Force Datamentioning
confidence: 99%
See 2 more Smart Citations
“…To do so, we measured head dimensions of every specimen, log 10 -transformed them, and calculated the mean distance between males and females along the first axes of a PCA. This measure of sexual dimorphism in head dimensions was previously demonstrated to be a good indicator for the level of sexual competition in these populations (Taverne et al 2020). In vivo bite force was measured for all individuals as described in Taverne et al (2020).…”
Section: Specimens Ecological and Bite Force Datamentioning
confidence: 99%
“…Bite force and muscle data were log 10 -transformed, proportions of the type of food consumed (e.g., plants, hard arthropods) were arcsine-transformed, and the homogeneity of variances and normality of the distribution of the residuals were verified using Bartlett and Shapiro tests, respectively. For anal-yses including phylogeny we used a previously published tree describing the relationships between the populations in this study system (see Taverne et al 2020). Preliminary genomic analyses (Sabolić et al in preparation) indicated that there is effectively no gene flow between populations, and thus treating them as independent evolving lineages for phylogenetic comparative analyses is justified.…”
Section: Statistical Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the way in which morphological variation may affect bite force is species-specific, probably reflecting the different selective pressures operating on two closely species. 35 Nevertheless, further research is needed to identify the exact reasons for the similarity in bite force between scaly-breasted munias and white-rumped munias.…”
Section: Discussionmentioning
confidence: 99%
“…Different prey communities, their abundance and seasonal variation on islands impose changes in a lizard’s dietary niche and often lead to the utilization of novel resources 22 , a powerful driver of morphological evolution. Head size (width and height) is known to be associated with bite force, which in turn is related to foraging, mating, and fighting 13 , 23 . Discerning between these factors is difficult but essential to disentangle the evolutionary processes driving morphological variation in different ecological contexts 24 .…”
Section: Introductionmentioning
confidence: 99%